The Comparison of Computer Navigation and Robotic-assisted Total Knee Arthroplasty: A Review of Current Literature - Chia-Chun Hsia; De-Yi Liu; Nien-En Ku; Jui-Feng Chen; Shih-Chan Hsu; Shu-Jui Kuo (Formosan Journal of Musculoskeletal Disorders)
This review aimed to assess the existing evidence regarding the comparison between robotic-assisted (RA) and computer navigation (CN) total knee arthroplasty (TKA). Our study commenced on August 25, 2023, utilizing a methodological approach that combined textual descriptors with MESH terminologies. The search terms employed were as follows: “robotic arm-assisted total knee arthroplasty,” “robotic assisted total knee arthroplasty,” “robotic knee arthroplasty,” and “robotic-assisted primary total knee arthroplasty,” in conjunction with “computer assisted total knee arthroplasty,” “computer assisted knee arthroplasty,” and “computer assisted primary knee arthroplasty.” Studies focusing on revision arthroplasty or unicompartmental arthroplasty were excluded from the consideration. A total of eight studies were included in this review. The cited positive comparative study findings indicated that RA was associated with reduced surgical time, improved final alignment, and a shorter hospitalization duration compared to CN. RA-TKA patients exhibited superior range of motion and reduced pain scores on the 1st day following surgery. Narcotic usage was lower for the RA-TKA group on the 2nd day. Notably, the total morphine equivalent dose was also significantly lower for the RA-TKA group in comparison to the CN-TKA group. The risk of periprosthetic join infection was comparable between the two techniques. It is crucial to acknowledge that while these significant intra-group findings are notable, they may not apply universally across all studies. Consequently, it is imperative for future research to provide further support through higher-quality studies.